Coassembled Nanoparticles Composed of Functionalized Mesoporous Silica and Pillar[5]arene‐Appended Gold Nanoparticles as Mitochondrial‐Selective Dual‐Drug Carriers. (30th July 2020) - Ahn, Junho; Jin, Hanyong; Park, Jaehyeon; Lee, Boeun; Ok, Mirae; Lee, Ji Ha; Bae, Jeehyeon; Jung, Jong Hwa
Abstract: Coassembled nanoparticles composed of functionalized mesoporous silica and pillar[5]arene‐appended Au nanoparticles obtained through the formation of a host–guest complex are designed and synthesized as a mitochondrial‐selective dual‐drug delivery system. A pyridinium‐based ligand and fluorescein isothiocyanate are immobilized onto mesoporous silica to act as the mitochondria‐targeting ligand and fluorescence tracker, respectively, of a material dubbed NP‐3. Carboxylated pillar[5]arene‐capped Au nanoparticles (CP‐AuNPs) are fabricated by the templated reduction of Au 3+ . Interestingly, coassembled nanoparticles (NP‐1) composed of doxorubicin (DOX) loaded NP‐3 and CP‐AuNPs are then prepared via the formation of a host–guest complex between the pyridinium‐based ligand of NP‐3 and the pillar[5]arene of CP‐AuNPs. To demonstrate the effectiveness of NP‐2 and NP‐1 as mitochondrial targeting drug delivery systems, DOX and F16 are employed as model drugs. These drugs loaded onto NP‐2 and CP‐AuNPs, respectively, are selectively delivered to mitochondria, indicating the usefulness of NP‐2 and CP‐AuNPs as mitochondrial‐specific drug‐delivery carriers in cancer cells. More interestingly, the use of NP‐1 is also associated with the selective accumulation of DOX and F16 in mitochondria. The selective mitochondrial‐targeting of NP‐1 is possible by NP‐2 and F16 exposed to the cytoplasm, allowing the codelivery of the two drugs to the mitochondria. Abstract : Coassembled nanoparticles (NP‐1) composed of functionalized mesoporous silica and pillar[5]arene‐appended Au nanoparticles obtained through the formation of a host–guest complex selectively deliver doxorubicin and F16 as anticancer drugs to mitochondria in HeLa cells.